2012
DOI: 10.1161/circulationaha.112.104059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Everolimus-Eluting and Sirolimus-Eluting Coronary Stents

Abstract: on behalf of the RESET InvestigatorsBackground-Several recent randomized trials comparing everolimus-eluting stent (EES) and sirolimus-eluting stent (SES) reported similar outcomes. However, only 1 trial was powered for a clinical end point, and no trial was powered for evaluating target-lesion revascularization. Methods and Results-Randomized Evaluation of Sirolimus-eluting versus Everolimus-eluting stent Trial is a prospective multicenter randomized open-label trial comparing EES with SES in Japan. The trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 147 publications
(53 citation statements)
references
References 24 publications
0
52
1
Order By: Relevance
“…Although we could not demonstrate a difference in the angiographic outcomes in each baseline, EES exhibited better angiographic outcomes against the lesions in patients with chronic hemodialysis 16) and diabetes treated with insulin, 17) the most disadvantageous lesions for SES. 18,19) These would be attributable to the present better angiographic outcomes of EES by attenuating the impact of those factors on the present angiographic endpoints.…”
Section: Discussioncontrasting
confidence: 75%
“…Although we could not demonstrate a difference in the angiographic outcomes in each baseline, EES exhibited better angiographic outcomes against the lesions in patients with chronic hemodialysis 16) and diabetes treated with insulin, 17) the most disadvantageous lesions for SES. 18,19) These would be attributable to the present better angiographic outcomes of EES by attenuating the impact of those factors on the present angiographic endpoints.…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore, the FMJ approach with new DES seems to have better long-term outcomes compared with previous DES. However, most randomized trials comparing sirolimus-eluting stents with everolimus-eluting stents showed similar efficacy and safety outcomes [15,16]. In our study, sirolimus-eluting stents were predominantly used.…”
Section: Discussionmentioning
confidence: 67%
“…The designs and the 3‐year clinical outcomes of RESET and NEXT have been previously described in detail 5, 6, 7. In short, both RESET and NEXT are prospective, multicenter, randomized “DES versus DES” trials, in which eligible patients were randomly assigned to undergo percutaneous coronary intervention (PCI) with either everolimus‐eluting stents (EES; Xience V, Abbott Vascular, CA/PROMUS, Boston Scientific, MA) or sirolimus‐eluting stents (Cypher/Cypher select/Cypher Select‐plus; Cordis Corporation, Johnson and Johnson, NJ) in the RESET, and with either biolimus‐eluting stents (Nobori, Terumo, Tokyo) or EES in the NEXT.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative and quantitative coronary angiography (QCA) were assessed utilizing CAAS 5.9 (Pie Medical Imaging, Maastricht, Netherlands). Details of the angiographic analysis were previously presented 5, 6. In a subset of patients enrolled in the angiographic substudy, follow‐up angiography was performed between 240 and 365 days after the index PCI procedure in both the RESET and NEXT trials 7.…”
Section: Methodsmentioning
confidence: 99%